How Does Genuineness-Substance (Cheng-Ti) Act?: A Clarification of the Phenomenon of Genuineness Based onZhong Yong. - Lu, Yinghua (Dao: A Journal of Comparative Philosophy, 2021)
Based on the text Zhong Yong 中庸 (Right and Norm), this article clarifies the phenomenological experience of genuineness (cheng 誠). The Introduction presents the discussion of genuineness-substance from Zhou Dunyi 周敦頤 and Mou Zongsan 牟宗三, pointing out their omission of the concrete activity of genuineness. Section 2 explains concepts such as ti 體 (noumenon, substance, and original status), the endowment of Heaven, the original nature (xing 性), right (zhong 中), norm (yong 庸), with an indication that genuineness denotes keeping and developing an original status. Section 3 then shows that the original status of human nature is the endowment of emotion, reason, will, and so on, and the original status of the Heavenly way is the tendency of [ceaseless] growing. Under a holistic view, Section 4 expounds in detail the meaning of the statements "from genuineness to illumination" and "from illumination to genuineness" by making use of the distinction between nascent genuineness and refined genuineness. Section 5 reveals the creativity of genuineness in terms of the activating effect, which is caused by human beings' exertion of their potentials. From the perspective of Zhong Yong, this section also demonstrates the inner logic by which Neo-Confucianism is developed and differentiated into the learning of the heart-mind (xinxue 心學) and the learning of pattern (lixue 理學). This section also examines whether or not Zhu Xi's 朱熹 doctrine is unorthodox, as Mou Zongsan proposes.